red and white kop!
Junior Member
- Joined
- Jun 15, 2009
- Messages
- 231
this problem involves Pascal-sequence notation and i'm not sure how to do that, so i will use (n r)
(n r) = n!/(r! x (n-r)!)
assuming this is true, show that (n r)=(n (n-r)).
so basically i have to prove n!/(r! x (n-r)!)=(n (n-r))
i don't know if its useful to develop extensively but i did and it is unclear to me how to combine the two sequences in the denominator of the LHS
all help appreciated
(n r) = n!/(r! x (n-r)!)
assuming this is true, show that (n r)=(n (n-r)).
so basically i have to prove n!/(r! x (n-r)!)=(n (n-r))
i don't know if its useful to develop extensively but i did and it is unclear to me how to combine the two sequences in the denominator of the LHS
all help appreciated